Utilizing feed sequencing to decrease the risk of porcine epidemic diarrhea virus (PEDV) cross-contamination during feed manufacturing - Schumacher, L. L.; Cochrane, R. A.; Woodworth, Jason C.; Huss, A. R.; Stark, Charles R.; Jones, Cassandra K.; Chen, Q.; Main, R.; Zhang, J.; Gauger, P. C.; Dritz, Steven S.; Tokach, Michael D. (My University, 2016)
Since the introduction of porcine epidemic diarrhea virus (PEDV) into the United States, feed has been identified as a vector of transmission between herds. As with other biological hazards, biosecurity at feed manufacturing facilities plays a key role in preventing cross-contamination of finished feeds. One potential method for reducing introduction of PEDV into finished feeds is through batch sequencing of diets. Therefore, the objective of this study was to determine the effects of feed batch sequencing on PEDV cross-contamination between diets. A 50 kg batch of feed was inoculated with PEDV, mixed in a 0.11 m3 electric paddle mixer and had a final concentration of 4.5 × 104 TCID50 PEDV particles per g, cycle threshold (Ct) of 11. After mixing, the feed was discharged from the mixer into a bucket elevator and collected to mimic processing in a commercial feed mill. To simulate batch sequencing, 4 subsequent PEDV-free batch diets were processed through the system without equipment cleaning. Sequenced batches (1–4) were mixed, discharged, and sampled similar to the PEDV-positive batch. Feed inoculation, processing, and batch sequencing was performed for 3 replicates with complete PEDV-decontamination of all equipment and facility between each replication. All collected feed samples were analyzed for PEDV RNA by quantitative PCR (qPCR) and infectivity by bioassay. Bioassay included a controlled challenge study using 30 crossbred 10 d old pigs to establish infectivity. All pigs (9/9) challenged with the positive treatment (feed Ct 31.7 ± 0.20 SEM) had fecal swabs with detectible PEDV RNA indicating PEDV infectivity. Infectivity was further confirmed with histopathology and immunohistochemistry (IHC). The discharge for the first sequence had less detectable PEDV RNA (P < 0.01, feed Ct 39.1 ± 3.4 SEM). Feed samples from the second, third and fourth sequence had no detectable PEDV RNA (Ct > 45). Infectivity was confirmed in 1 of 3 replicate batches for the first and second sequences. It is important to note, the 2ndsequence did not have detectable PEDV RNA in any feed sample. The results of this study confirm feed as a vector of PEDV transmission and is the first to demonstrate feed without detectible PEDV RNA can be infective. Furthermore, although subsequent feed batches had reduced quantities of PEDV RNA, they were still found to be infective. Therefore, feed batch sequencing should be considered a risk mitigation strategy but should not be considered a risk elimination strategy.
Citation: Schumacher, L. L., Cochrane, R. A., Woodworth, J. C., Huss, A. R., Stark, C. R., Jones, C. K., . . . Tokach, M. D. (2016). Utilizing feed sequencing to decrease the risk of porcine epidemic diarrhea virus (PEDV) cross-contamination during feed manufacturing. Journal of Animal Science, 94, 76-76. doi:10.2527/msasas2016-163
Keywords: Feed; Pedv; Sequencing; Agriculture